Design and analysis of radially polarized screen-printed piezoelectric transducers. (April 2017) - Salowitz, Nathan Picchietti; Kim, Sang-Jong; Kopsaftopoulos, Fotis; Li, Yu-Hung; Chang, Fu-Kuo
Piezoelectric transducers have applications from ultrasonic structural health monitoring to micro-electromechanical systems. Small physical size coupled with large actuation is desirable in many applications, requiring unique transducer designs to take advantage of the material properties. Screen-printed piezoceramics were developed as a means of mass producing mezzo-scale transducers that are geometrically small and light weight, but large enough to generate significant actuation. Screen-printed piezoceramic transducers display significantly different properties than chemically identical bulk ceramic elements, largely attributed to high void fraction of screen-printed piezoceramic materials and detrimental to the functionality of traditional transducer designs. This article presents analysis, simulation, and initial testing of new designs for screen-printed piezoceramic transducers with concentric through-thickness electrodes. Analytical models were developed enabling analysis across material properties and design parameters. Analytical results were verified against finite element models for some designs. Prototypes were created and underwent initial testing to assess the properties of the design.